1970
DOI: 10.1172/jci106318
|View full text |Cite
|
Sign up to set email alerts
|

On the influence of extracellular fluid volume expansion and of uremia on bicarbonate reabsorption in man

Abstract: A B S T R A C T The patterns of bicarbonate reabsorption during increasing plasma concentrations were studied in subjects with a range of glomerular filtration rates (GFR) from 170 to 2 ml/min. In a group of five subjects with GFR values above 30 ml/min, paired bicarbonate titration studies were performed first under conditions which minimized extracellular fluid (ECF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 8 publications
(9 reference statements)
2
31
0
Order By: Relevance
“…Bicarbonate Ringer's expansion predictably decreased hematocrit and plasma protein concentration (Table II). When tubules were perfused with 24 mM bicarbonate 5 In the calculation of a driving force for bicarbonate diffusion, PD was not included. Using a similar perfusate, Fromter et al (16) have measured a transepithelial PD of +1.4 mV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bicarbonate Ringer's expansion predictably decreased hematocrit and plasma protein concentration (Table II). When tubules were perfused with 24 mM bicarbonate 5 In the calculation of a driving force for bicarbonate diffusion, PD was not included. Using a similar perfusate, Fromter et al (16) have measured a transepithelial PD of +1.4 mV.…”
Section: Resultsmentioning
confidence: 99%
“…Clearance studies in dogs, rats, and man have all demonstrated that ECF volume expansion inhibits fractional bicarbonate reabsorption (3)(4)(5)(6)8). A prevalent view has been that this inhibition occurs in the proximal tubule and is related to increased bicarbonate back leak (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But still other possible mechanisms may be involved, as previously mentioned (25). Enforced activity of cellular Na ϩ /H ϩ exchangers (18,36) as well as Na ϩ /H ϩ ion exchanges on the extracellular glycosaminoglycans (19) and/or a Na-induced expansion of extracellular volume, resulting in a decrease in HCO 3 Ϫ reabsorption (3,38,52,58), can contribute to mediation of the effect of NaCl on acid-base balance. Summarizing, with high NaCl intake, renal loss of bicarbonate but also excess acid production could be reasonably expected to affect acid-base status.…”
Section: Discussionmentioning
confidence: 98%
“…The former would be due to hypoventilation, often seen in patients with hypophosphatemia (ll, 12); and the latter due to dehydration-induced secondary aldosteronism. The high urine pH may be explained by the overflow of HCO3~ which was exaggerated by the rehydration (13). Although elevated GOT, GPT, LDH, ALP, and BUN in the serum were corrected successfully by intravenous nutrition (400-800kcal/day) and fluid (1,600-2,500 ml/day) administration, serum phosphate concentration decreased drastically, and acute renal failure followed (Fig.…”
Section: Case Reportmentioning
confidence: 97%